Analysis of Trapped oscillation modes in magnetized plasma photonic crystal using one dimentional modeling - Mittal, Tanvi (My University, 2016)
Dissertation presents the analysis and simulation of magnetized binary plasma photonic crystal (PPC) using 1-D mathematical modeling, where trapped oscillation in photonic bandgap (PBG) has been highlighted using dispersion relation and transmittance characteristics. A comparative study on binary and ternary magnetized PPC has also been presented based on the PBG characteristics. The PPC constitutes the periodic structure of plasma and dielectric layers, where the propagation of electromagnetic waves depends on effective plasma frequency (EPF). It is the lowest frequency of wave which can pass through the PPC structure. The presence of plasma layer in PPC provides wide tunability of EPF and this enables to tune the PPC electronically for desired PBG in a very fast manner by varying magnetic field, electronic concentration and thickness of plasma layer. This theory is explained in detail in thesis through the analysis of binary and ternary magnetized PPC and it is found that the value of EPF is lower for ternary PPC as compared to the binary one and this difference could be more significant when more number of layers is structured. Also, the presence of static magnetic field provides extraordinary mode in plasma that yields to trapped oscillations and introduces undesirable discontinuity in the PBGs. This is found to be mainly dependent on applied magnetic field, electronics concentration and hybrid frequency and can be shifted to any other position in a prescribed frequency band by having suitable values of these parameters. This property in PPCs can be utilized for the design of filters in millimeter range and in military applications, viz. to prevent the spoofing of signals from enemies, during communication.
Keywords: Photonic Crystal, PBG, PPC